NON-ENGLISH MAJOR STUDENTS’ FOREIGN LANGUAGE ANXIETY: A STUDY CASE - Leni Rohliah; Pratiwi Lestari; Wirda Ningsih; Genta Ulina Hutagalung (Universitas Indo Global Mandiri, 2023)
In learning English students might face some obstacles that made them reluctant to improve their competence. One of the obstacles was the existence of language anxiety that students could experience in learning English. The objective of this research was to find out the descriptions of non-English major students’ foreign language anxiety which consisted of communication apprehension, fear of negative evaluation, test anxiety, and English classroom anxiety. This research used a qualitative research method, in which the writers did a study case at one university in Palembang. The data were analyzed descriptively and presented in tables. In this research, 640 first semester students of Economics and Business Faculty of Muhammadiyah University Palembang in the academic year of 2021/2022 were chosen by using the total population sampling. The data were collected by using Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire. Based on the findings of the research, it showed that students experienced foreign language anxiety, such as communication apprehension, fear of negative evaluation, test anxiety, and English classroom anxiety.